Between the Biennials: Cultural Networks in Times of Geopolitical Crisis - Carmen Lael Hines; Helge Mooshammer; Peter Mörtenböck (OBOE)
This essay unpacks key issues of transnational curatorial collaboration that emerged during the Biennale Architettura 2021, a high-profile cultural event marked by the uncertainties and challenges of the COVID-19 pandemic. The article places particular focus on the happenings of the Curators Collective, a coalition of national pavilion curators formed in relation to this particular Biennale, as a case study for considering the tensions and possibilities that come with mutually supportive networks in the context of international cultural exhibition events. We Like, the Austrian contribution to the 2021 Venice Architecture Biennial, dedicated to platform urbanism, became a site of transnational curatorial collaboration and is discussed in the article to contextualise the numerous projects and events of the first Biennale Architettura Midissage (August 27-29, 2021), jointly organised by several dozen national pavilions to fulfil the Biennale’s potential as a platform for synergistic collaboration, solidarity, and accessibility.